Differential Brain and Muscle Tissue Oxygenation Responses to Exercise in Tibetans Compared to Han Chinese - Fan, Jui-Lin; Wu, Tian Yi; Lovering, Andrew T.; Nan, Liya; Bang, Wang Liang; Kayser, Bengt (Frontiers in Physiology, 2021)
The Tibetans' better aerobic exercise capacity at altitude remains ill-understood. We tested the hypothesis that Tibetans display better muscle and brain tissue oxygenation during exercise in hypoxia. Using near-infrared spectrometry (NIRS) to provide indices of tissue oxygenation, we measured oxy- and deoxy-haemoglobin ([O2Hb] and [HHb], respectively) responses of the vastus lateralis muscle and the right prefrontal cortex in ten Han Chinese and ten Tibetans during incremental cycling to exhaustion in a pressure-regulated chamber at simulated sea-level (air at 1 atm: normobaric normoxia) and 5,000 m (air at 0.5 atm: hypobaric hypoxia). Hypoxia reduced aerobic capacity by ∼22% in both groups (d=0.8, p<0.001 vs. normoxia), while Tibetans consistently outperformed their Han Chinese counterpart by ∼32% in normoxia and hypoxia (d=1.0, p = 0.008). We found cerebral [O2Hb] was higher in Tibetans at normoxic maximal effort compared Han (p = .001), while muscle [O2Hb] was not different (p=0.240). Hypoxic exercise lowered muscle [O2Hb] in Tibetans by a greater extent than in Han (interaction effect: p<0.001 vs normoxic exercise). Muscle [O2Hb] was lower in Tibetans when compared to Han during hypoxic exercise (d=0.9, p =0.003), but not during normoxic exercise (d=0.4, p=0.240). Muscle [HHb] was not different between the two groups during normoxic and hypoxic exercise (p=0.778). Compared to Han, our findings revealed a higher brain tissue oxygenation in Tibetans during maximal exercise in normoxia, but lower muscle tissue oxygenation during exercise in hypoxia. This would suggest that the Tibetans privileged oxygenation of the brain at the expense of that of the muscle.